HIJAB DAN EMANSIPASI PEREMPUAN DI DUNIA KERJA - Herawati, Yunie (Faculty of Humanities, Diponegoro University, 2011)
Moslem women is instructed by Quran and the prophet to cover their bodies with hijab. This instruction is based on the religious duty for every moslem woman to keep her honor while practicing her important role in the society. Recognizing that Islam pays respect and does teach gender equality and woman’s basic rights, hijab should be in no way limiting women’s freedom both in daily life or professional career like many accusers of hijab argue. Islam views women as having an equal position with men in jihad, worship, and work, while still maintaining their honor and religious duties. Even in this modern era, hijab may become a symbol of one’s (woman’s) conscious chosen identity, faith, and integrity. Keywords: hijab, gender equality, basic woman rights